"For some people it isn't a choice, it's just how it happens": Accounts of "delayed" motherhood among middle-class women in the UK. (May 2016) - Budds, Kirsty; Locke, Abigail; Burr, Vivien
Over the past few decades the number of women having their first babies over the age of 35 in the United Kingdom has increased. Women's timing of motherhood is invariably bound up with a discourse of "choice", and in this paper we consider the role choice plays in the timing of motherhood among women who have been defined as "older" mothers. This article is based on data from 11 semi-structured interviews that explored the transition to motherhood among "older" middle-class mothers. The interviews were analysed using critical discursive psychology. The women drew upon two dominant repertoires when making sense of their timing of motherhood. Within the first repertoire, "older motherhood as circumstance", older motherhood was presented as the outcome of life circumstances beyond their control, with a lack of the "right" circumstances facilitating "delayed" motherhood. Within the second repertoire, "older motherhood as readiness", women constructed themselves as (now) prepared for motherhood. "Readiness" was bound up with notions of self-fulfilment, yet also assessments of their ability to be "good" mothers. We conclude that, far from a straightforward choice, the timing of motherhood is shaped by cultural definitions of the "right" circumstances for parenthood, but also cultural definitions of "good" motherhood, which may define when women are "ready".